Prevention of Chronic Non-transmissible Diseases: Regarding a Reflection - Aliuska Tamayo Verdecia (Revista Finlay)
The University Medical Sciences, higher education center, responsible for training the health professionals for the province, has to be the health prevention and promotion protagonist activities. It would be advisable to insert this teaching institution in the Cienfuegos Global Project, because through the execution of is designed community interventions which can be undertaken by academics and students; it will not only contribute to the significant target of guaranteeing a healthier life expectancy in the Cienfuegos population, but also to educate students increasingly aware of the current problems of our society.